8 Years of institutional assessment feedback: students' satisfaction with library services. Issue 4 (13th November 2017) - Rysavy, Monica D.T.; Michalak, Russell; Wessel, Alison
Abstract : Purpose: The purpose of this paper is to examine eight years of quantitative and qualitative student feedback on library services collected through an institution-wide student satisfaction survey. Design/methodology/approach: This paper utilizes data collected during an eight-year period from the college's student satisfaction survey. This survey contained 40 questions which addressed topics concerning the college's 13 major departments. Six of the questions were devoted to library services. Findings: Over the eight years surveyed, across all divisions surveyed (undergraduate students, graduate students and graduate Saturday students), students on average tended to select "agree" or "strongly agree" with the following six questions asked: The materials in the library meet my course requirements. The library has enough laptop computers for student use. The instructional materials for using the online databases are helpful. The library hours match my schedule and needs. The library equipment is in good working order. The library is generally quiet and suitable for study. Originality/value: This institutionally crafted, mixed methods survey was deployed over an eight-year period at a relatively minimal cost (in-house staff hours were used to analyze the data gathered and paper Scantron sheets were used to deploy). Furthermore, rich data were gathered from a relatively simple instrument and this information was used to make institution-wide decisions.